Valuing environmental impacts of coastal development projects: A choice experiment application in Spain - David Hoyos; Pere Riera; Javier Fernández-Macho; Carmen Gallastegui; Dolores Garcia (African Journal of Environmental Economics and Management, 2013)
This paper presents the results of an empirical application aimed at estimating the economic value of the potential environmental impacts to mount Jaizkibel (Spain) resulting from the construction of a new seaport over its hillside. A choice experiment technique is applied for an ex-ante natural resource damage assessment in monetary terms. The results revealed that, depending on the extent of the environmental damage, the social welfare loss would be between 172 and 535 million Euros per annum.